دلالة إشارة النص وآثارها في فهم النصوص الشرعية والقوانين الوضعية - Prihantoro, Hijrian A. (Indonesian Journal of Interdisciplinary Islamic Studies (IJIIS), 2017)
THE INDICATION OF TEXTS' SIGNAL AND ITS IMPACT ON THE UNDERSTANDING OF SHARI'A AND POSITIVE LAWS AbstractThis paper aims to discuss one of the meanings of the words, namely the Indication of the Text Evidence in terms of its concept and how it is used in the process of deriving judgments from the texts of Islamic jurisprudence and the texts of the positive laws. This paper deals with an analytical study through the indication of the text evidence from the Holy Qur'an and the Sunnah, and the Jordanian Laws, in particular, the Jordanian Civil Code, the Jordanian Evidence Law and the Jordanian Personal Status Law. It decides the importance of this research, which is one of the terms of the Islamic legal theory including the benefits of its rules and an important task that is indispensable to the scholar instead of denying it, whether he is a man of the Islamic jurisprudence or a man of positive law. Keywords: The Indication of the Text’s Signal, Sharia, Positive Laws.